Temporal and spatial heterogeneity of recent lake surface water temperature trends in the Qinghai-Tibet Plateau. Issue 25 (13th December 2022) - Yao, Tianci; Lu, Hongwei; Yu, Qing; Feng, Wei; Xue, Yuxuan; Feng, Sansan; Xiao, Shuai
Abstract: Lake surface water temperature (LSWT) monitoring is significant as it provides valuable information on climate changes and resultant changes in lakes. Here, monthly moderate resolution imaging spectroradiometer LSWT data of 364 lakes during 2001–2015 were analysed to determine spatiotemporal patterns of daytime (LSWTd ), nighttime (LSWTn ), daily LSWT (LSWTm ) and their drivers in the Qinghai-Tibet Plateau at monthly, seasonal and annual timescales. We focused on spatiotemporal heterogeneity of LSWT trends. Results showed climatological LSWT presented a saddle-shaped distribution along the northeast-southwest direction except for LSWTd in March, while highly heterogeneous LSWT trends without spatial dependence were observed at all timescales. Diurnal asymmetry of LSWT trends was evident with 56.04–88.19% lakes showing smaller LSWTd trends than LSWTn trends except for August and September. Further, we found lake surface albedo trend could effectively explain spatial patterns of LSWT trends at different timescales, and its interactions with other variable trends generally were the largest or second-largest.